“PLAN DE SEGURIDAD Y SALUD OCUPACIONAL EN LA PLANTA PROCESADORA DE ARROZ DE LA INDUSTRIA COHERBUR, EN EL CANTÓN CATAMAYO, CIUDAD DE LOJA, PERIODO OCTUBRE 2019 – MARZO 2020” - Castillo Suing, Yesenia Maribel (2021)
This research work was developed in the Province of Loja, in the Canton Catamayo, in the Coherbur Rice Processor, with the general objective of presenting a proposal for an occupational health and safety plan, in order to improve health in work, mitigate the possible risks that may occur within the company and generate a culture of prevention in workers. The theoretical arguments of the present investigation are properly supported and the information sources are cited. The methods used are: inductive, descriptive and analytical, and the techniques used are: the interview directed to Mr. Ángel Burí, manager of the Rice Processor - Coherbur and the surveys applied to administrative employees and workers with the aim of preparing a Current diagnosis on occupational health and safety, which allowed to know the activities of the workers of the Rice Processor - Coherbur, and also to identify the existing work areas. The data obtained allowed us to conclude that there is no Occupational Health and Safety management, likewise there is no good physical condition for the workers, therefore, they do not use personal protective equipment (PPE), and they do not there is a constant training program to expand your knowledge of occupational health and safety From the information obtained through the interview, the manager of the Rice Processor - Coherbur was able to state that the company does not have an occupational health and safety plan. Once the situational analysis of the Rice Processor - Coherbur was completed, the conclusion was reached of the need for a proposal for an Occupational Health and Safety Plan, which will contribute to decision- making to prevent incidents, accidents and occupational diseases of Workers. Finally, a recommendation was made to consider the implementation of this Plan, the frequent training of employees and the updating of the Joint Committee.